2014
DOI: 10.1371/journal.pone.0101959
|View full text |Cite
|
Sign up to set email alerts
|

Areca Nut Components Affect COX-2, Cyclin B1/cdc25C and Keratin Expression, PGE2 Production in Keratinocyte Is Related to Reactive Oxygen Species, CYP1A1, Src, EGFR and Ras Signaling

Abstract: AimsChewing of betel quid (BQ) increases the risk of oral cancer and oral submucous fibrosis (OSF), possibly by BQ-induced toxicity and induction of inflammatory response in oral mucosa.MethodsPrimary gingival keratinocytes (GK cells) were exposed to areca nut (AN) components with/without inhibitors. Cytotoxicity was measured by 3-(4,5-dimethyl- thiazol- 2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay. mRNA and protein expression was evaluated by reverse transcriptase-polymerase chain reaction (RT-PCR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…The aberrant growth, differentiation, and inflammation of gingival keratinocytes induced by these pathways may contribute to the pathogenesis of oral submucous fibrosis and OSCC. 18 In the present study, CYP1A1 was only expressed in peripheral cells of the invasive front near blood vessels and nerve fibres, suggesting that this enzyme contributes to tumour aggressiveness in both groups.…”
Section: Discussionsupporting
confidence: 44%
“…The aberrant growth, differentiation, and inflammation of gingival keratinocytes induced by these pathways may contribute to the pathogenesis of oral submucous fibrosis and OSCC. 18 In the present study, CYP1A1 was only expressed in peripheral cells of the invasive front near blood vessels and nerve fibres, suggesting that this enzyme contributes to tumour aggressiveness in both groups.…”
Section: Discussionsupporting
confidence: 44%
“…productions that are potential tumor promoters. 7,12,21,30,31 Prostaglandin and ROS have been demonstrated to promote the transformation of carcinogen and radiation-treated C3H10T1/2 cells. 32,33 Moreover, we found that ANE markedly stimulated the transformation of C3H10T1/2 cells, especially in the presence of the tumor promoter, TPA.…”
Section: Discussionmentioning
confidence: 99%
“…The areca nut component of betel quid plays a major role in the pathogenesis of oral submucous fibrosis. [10,11,12,13] In a 2004 study, a clear dose-dependent relationship was observed for both frequency and duration of chewing areca nut (without tobacco) in the development of oral submucous fibrosis. [14] Smoking and alcohol consumption alone, habits common to areca nut chewers, have been found to have no effect in the development of oral submucous fibrosis, [15] but their addition to areca nut chewing can be a risk for oral submucous fibrosis.…”
Section: Introductionmentioning
confidence: 99%